2017
DOI: 10.1186/s12871-017-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different infusion rates of sufentanil on surgical stress index during cranial pinning in children under general anaesthesia: a randomized controlled study

Abstract: BackgroundSurgical stress index (SSI) is an established indicator for intraoperative nociception. Opioids are used to block stimulus of cranial pinning in neurosurgery. We investigated the effect of different infusion rates of sufentanil on SSI during cranial pinning in children under general anaesthesia.MethodsForty-nine children (2–12 years of age) underwent neurosurgery with pinning. The children were randomized into three groups based on the rate of sufentanil infusion: 0.2, 0.5, and 0.8 μg·kg−1·hr.−1. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Sufentanil takes nearly 45 minutes to achieve a steadystate between plasma concentrations and effect-site concentrations, so we chose to administrate sufentanil 1h before the end of the surgery (usually when the last myomas was begin to be removed) 23,24 Patients were sent to the operation room without any premedication, then the left lower limb peripheral veins were opened and compound sodium lactate solution 4-6 mL/kg/h was infused. Standard monitoring, including five-lead electrocardiography (ECG), pulse oxygen saturation (SpO 2 ), and noninvasive blood pressure (NBP), was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufentanil takes nearly 45 minutes to achieve a steadystate between plasma concentrations and effect-site concentrations, so we chose to administrate sufentanil 1h before the end of the surgery (usually when the last myomas was begin to be removed) 23,24 Patients were sent to the operation room without any premedication, then the left lower limb peripheral veins were opened and compound sodium lactate solution 4-6 mL/kg/h was infused. Standard monitoring, including five-lead electrocardiography (ECG), pulse oxygen saturation (SpO 2 ), and noninvasive blood pressure (NBP), was performed.…”
Section: Methodsmentioning
confidence: 99%
“…After allocation, both patients and investigators were blinded to the interventions. Sufentanil takes nearly 45 minutes to achieve a steady-state between plasma concentrations and effect-site concentrations, so we chose to administrate sufentanil 1h before the end of the surgery (usually when the last myomas was begin to be removed) 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the ability of the SPI to provide not only detection but also a quantitative assessment of nociception in children is still debated. In 2–12 years old children, using different infusion rates of sufentanil during cranial pinning had no effect on SPI levels [23]. The administration of atropine as a systematic premedication, and the variety of anesthetic agents used during the procedure might limit the interpretation of these results.…”
Section: Surgical Pleth Indexmentioning
confidence: 96%
“…In contrast, limitations have been reported for various clinical situations and confounding factors [ 18 23 ], one of which may be age. Thus, limitations presented in the studies of pediatric patients must be considered carefully [ 19 , 24 , 25 ].…”
Section: Nociception Monitoring Tools Using Pulse Wave Amplitude and mentioning
confidence: 99%
“…Song et al [ 25 ] also reported there was no significant difference in SPI changes during cranial pin fixation among the groups received sufentanil infusion at three different rates (0.2, 0.5, and 0.8 μg/kg/h) in pediatric patients aged 2–12 years who underwent cranial pinning under general anesthesia, suggesting that SPI may not be sensitive enough to monitor a level of nociception and analgesia in children.…”
Section: Nociception Monitoring Tools Using Pulse Wave Amplitude and mentioning
confidence: 99%